Auricular Plaster Therapy for Comorbid Insomnia: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. (15th January 2019) - Zhao, Huimin; Li, Dan; Yang, Ying; Liu, Yueting; Li, Jie; Mao, Jing
Abstract : Background. Although the effectiveness of auricular plaster therapy (APT) on primary insomnia has been systematically reviewed, no systematic review of studies has focused on the effect on comorbid insomnia. Objective . To evaluate the efficacy and safety of APT for comorbid insomnia. Methods . Fifteen databases were searched from inception to July 2018. Randomized controlled trials (RCTs) of APT as an exclusive intervention for comorbid insomnia against Western medications, sham APT or no treatment were identified. Results. Fourteen studies involving 928 participants were identified. The pooled outcomes revealed that APT was superior to control conditions for the global score on PSQI (SMD = -1.13, and 95% CI = -1.48—-0.78) and the effective rate (RR = 1.24, 95% CI = 1.13—1.36, NNT = 5, and 95% CI =4—7). Furthermore, the results of subgroup analyses were similar to the pooled results. Additionally, the pooled results were verified to be stable by sensitivity analyses. Regarding safety, no significant difference was identified between APT and Western medications. Conclusions. APT appears to be an effective and safe treatment for comorbid insomnia. However, the benefits of APT for comorbid insomnia could not be ascertained due to the paucity of the quantity and quality of the included studies. Large-scale studies using proper methodology are needed to yield a firm conclusion.